Modelling the Relationship between Linked-In Usage and Social Capital Formation - Hoda, Najmul; Gupta, S. L.; Ahmad, Mobin; Gupta, Utkarsh (European Journal of Sustainable Development, 2021)
The main purpose of this study is to test if the use of social networking sites (SNSs) results in any perceived social capital for the users. Putnam’s classification of social capital into bridging and bonding social capital is used for the study. The first objective of the study was to study the demographic and behavioral profile of LinkedIn users. The second objective was to test the model describing the relationship between the constructs intensity of LinkedIn usage and the two types of social capital. A structured questionnaire that included standard scales for measuring the constructs was shared on various social media platforms. The model was analyzed using PLS-SEM in R software. The results confirmed all the three hypothesized relationships and also validated the overall model. This study contributes to the validation as well as extension of social capital theory in SNS. Further, the results throw light on the new applications of SNS by the industry.